Organizational Innovation and Substandard Performance: When is Necessity the Mother of Innovation? - Bolton, Michele Kremen (Organization Science, 1993)
This study extends earlier empirical research into organizational decline which has found that substandard performance stimulates innovation in a wide range of manufacturing industries. Using data from 74 U.S. high technology firms, this research investigates the relationship between organizational performance and adoption of an organizational innovation, the decision to join an R&D consortium. The central premise of the study is that a firm's propensity to innovate fluctuates with organizational performance, rather than stemming solely from a firm's inherent characteristics (such as size, structure, leadership, etc.). The study found that substandard performance stimulated early joiners of R&D consortia. More risk-averse, high performing firms were found to be late adopters of R&D consortia. However, the relationship between performance and innovation was somewhat more complex than traditionally envisioned. First, a distinct institutionalization effect occurred as R&D consortia became a commonly accepted method of conducting certain types of R&D projects. While substandard performance was necessary to stimulate the early adopters, over time, institutionalization of R&D consortia occurred, risks associated with adoption were lowered, and later adopters were no longer stimulated solely by substandard performance. Second, an adoption decision was observed to involve more than a single, dichotomous organizational choice, but included both an initial adopt/nonadopt component and a related decision involving the timing of adoption (early/late). The relationship between organizational performance and innovation emerged only when the effects of the initial adoption decision (adopt/nonadopt) were separated from the effects of adoption timing (early/late). The results here point rather strongly to the need to expand inquiry into the decision-making processes of late adopting firms, which are essentially “imitators,” to complement the existing prodigious literature on early adopting, firms, perceived in the traditional literature as “innovators.”